2011
DOI: 10.1038/ng.942
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a functional transposon insertion in the maize domestication gene tb1

Abstract: Genetic diversity created by transposable elements is an important source of functional variation upon which selection acts during evolution1–6. Transposable elements are associated with adaptation to temperate climates in Drosophila7, a SINE element is associated with the domestication of small dog breeds from the gray wolf8 and there is evidence that transposable elements were targets of selection during human evolution9. Although the list of examples of transposable elements associated with host gene functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
543
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 678 publications
(565 citation statements)
references
References 33 publications
19
543
0
3
Order By: Relevance
“…Furthermore, the 11.0-kb insertion, which probably occurred after the ectopic recombination event, may have led to the creation of the functional black rice promoter of Kala4 (Figure 3). Several functional polymorphisms that cause regulatory alterations have been reported to produce domestication traits (Konishi et al, 2006;Studer et al, 2011;Meyer and Purugganan, 2013;Chakrabarti et al, 2013;Xu et al, 2015). In the case of teosinte branched 1 in maize, an insertion of a transposon called Hopscotch acts as an enhancer of gene expression and contributed to the change in apical dominance of maize upon domestication (Studer et al, 2011).…”
Section: The Structural Change In the Promoter Of Kala4 Confers The Bmentioning
confidence: 99%
“…Furthermore, the 11.0-kb insertion, which probably occurred after the ectopic recombination event, may have led to the creation of the functional black rice promoter of Kala4 (Figure 3). Several functional polymorphisms that cause regulatory alterations have been reported to produce domestication traits (Konishi et al, 2006;Studer et al, 2011;Meyer and Purugganan, 2013;Chakrabarti et al, 2013;Xu et al, 2015). In the case of teosinte branched 1 in maize, an insertion of a transposon called Hopscotch acts as an enhancer of gene expression and contributed to the change in apical dominance of maize upon domestication (Studer et al, 2011).…”
Section: The Structural Change In the Promoter Of Kala4 Confers The Bmentioning
confidence: 99%
“…Expression of the dominant maize Tb1 allele is about 2-fold greater than the recessive teosinte allele (Doebley et al, 1997;Hubbard et al, 2002, Studer et al, 2011. A critical regulatory region is located between 58.7 and 69.5 kb upstream of the Tb1 coding sequence (Clark et al, 2006).…”
mentioning
confidence: 99%
“…A critical regulatory region is located between 58.7 and 69.5 kb upstream of the Tb1 coding sequence (Clark et al, 2006). Recent evidence has shown that two transposable element insertions in this essential region of the Tb1 gene are responsible for elevated expression of the maize Tb1 allele (Studer et al, 2011;Zhou et al, 2011). In maize, plant architecture derives from two types of branches that affect its agronomic utility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…mays) from its wild ancestor, teosinte (Z. mays L. subsp. parviglumis), and there has been strong selection at this locus during maize domestication (30). The tb1 locus, on chromosome 1, interacts with another locus on chromosome 3 to affect the sexuality of the inflorescences (31), and the allelic state of the chromosome 3 gene has a dramatic impact on tb1 effect size.…”
Section: Epistasis Affects Domestication and Crop Improvement Traitsmentioning
confidence: 99%